Economic Order Model (Q,R): Constant Lead Times And Exponential Backorder Costs (International Journal of Scientific Research and Management (IJSRM), 2014)
The paper considers the simple model of inventory models (Q,R) The backorder cost Cβ/t) is taken as an exponential function of t, the length of time of the backorder, Cβ(t) is b t b e 2 1 . The expected backorder cost is derived by obtaining the difference between the expected backorder cost at time t+L and t+L+T. In this paper demand is assumed to follow a normal distribution.Some basic mathematics of the properties of a normal distribution is introduced to simplify the derivation of the equations. The first order derivatives of the inventory backorder costs are given.